American Muslim patriots, Islam and U.S. military history - Muhammad, Ruthie Ayesha (Dorrance Publishing Co., Inc., 2010)
Lieutenant Commander Ruthie Ayesha Muhammad, an American Muslim and retired U.S. Navy officer, seeks to dispel the negative myths that question American Muslims' loyalty to our country, by highlighting American Muslims' contributions to the United State Armed Forces in her first book, American Muslim Patriots, Islam and U.S. Military History. In it, she outlines the history of Muslims in the American military and recounts the tales of a number of great Muslim patriots, many of whom fought and died for America. Through stories from her own experience and the experiences of others, Muhammad honors the memories of those Muslim military heroes and compels her readers to look beyond superficial prejudices. In doing so, one should see that duty to country is a quality determined not by religious belief or skin color and background, but by character.